Apply the Properties of Integer Exponents to generate equivalent expressions to 4^0 ⋅ 5^−2/(−2)^−3 with only positive exponents, then solve the expression. Your answer will be a simplified fraction with no remaining exponents.(1 point)

4^0 ⋅ 5^−2/(−2)^−3=

3 answers

Using the property of integer exponents that any number raised to the power of 0 is equal to 1, we can simplify 4^0 to 1.

4^0 ⋅ 5^-2/(−2)^−3

= 1 ⋅ 5^-2/(−2)^−3

Using the property of negative exponents, we know that a^-n = 1/a^n. So, we can rewrite 5^-2 as 1/5^2 and (−2)^−3 as 1/(-2)^3.

= 1 ⋅ 1/5^2/1/(-2)^3

Using the property of division, dividing by a fraction is equivalent to multiplying by its reciprocal. The reciprocal of 1/5^2 is 5^2/1, and the reciprocal of 1/(-2)^3 is (-2)^3/1.

= 1 ⋅ 1/5^2 * 5^2/1 * (-2)^3/1

Using the property of exponents that a^m * a^n = a^(m+n), we can combine the exponents with the same base.

= 1 * 1 * (-2)^3/1 * 5^2/1

= (-2)^3 * 5^2

= -8 * 25

= -200

So, the simplified expression is -200.
I apologize for the mistake. Let's try again!

Using the property of integer exponents that any number raised to the power of 0 is equal to 1, we can simplify 4^0 to 1.

4^0 ⋅ 5^-2/(−2)^−3

= 1 ⋅ 5^-2/(−2)^−3

Using the property of negative exponents, we know that a^-n = 1/a^n. So, we can rewrite 5^-2 as 1/5^2 and (−2)^−3 as 1/(-2)^3.

= 1 ⋅ 1/5^2/1/(-2)^3

Using the property of division, dividing by a fraction is equivalent to multiplying by its reciprocal. The reciprocal of 1/5^2 is 5^2/1, and the reciprocal of 1/(-2)^3 is (-2)^3/1.

= 1 ⋅ 1/5^2 * 5^2/1 * (-2)^3/1

Using the property of exponents that a^m * a^n = a^(m+n), we can combine the exponents with the same base.

= 1 * 1 * (-2)^3/1 * 5^2/1

= (-2)^3 * 5^2

= -8 * 25

= -200

So, the simplified expression is -200.

I apologize once again for the mistake, and thank you for bringing it to my attention.